Partnership after induced abortion: A prospective controlled study - Barnett, Winfried; Freudenberg, Nahid; Wille, Reinhard (Archives of sexual behavior, 1992)
To study the social and psychological consequences of induced abortion on the relationship between the pregnant woman and her partner, 92 patients seeking a socially indicated abortion, who had a stable partner at the time of abortion, were interviewed. Standardized psychological measures were used to assess their partnerships before abortion and on follow-up 1 year later. A control group of 92 patients (matched for age, marital status, duration of partnership, number of children, and educational background), drawn from a larger sample of women using safe contraceptive methods, completed the same psychological measures. Prior to abortion, partnerships in the study group showed considerably more conflicts and were less harmonious than in the control group. One year after the abortion, the number of separations in the study group was not significantly higher than in the control group, nor were there any remaining qualitative differences in the partnerships of either group. When separations occurred, they had been more frequently initiated by women in the study group than in the control group.